Mechanical and flammability characterisations of biochar/polypropylene biocomposites. (1st December 2016) - Das, Oisik; Bhattacharyya, Debes; Hui, David; Lau, Kin-Tak
Abstract: Biocomposites were manufactured with biochar and polypropylene at five loading levels (0, 15, 25, 30, and 35 wt%) by compounding and injection moulding. Biocomposites were tested by tension, bending, cone calorimeter, thermogravimetry, differential scanning calorimetry, X–ray diffraction, and infrared spectroscopy. Incorporation of increasing amount of biochar to neat polypropylene continuously improved its tensile modulus and flexural strength/modulus. The peak heat release rate and smoke production of the biocomposites were significantly reduced as a result of biochar addition. The high surface area of biochar allowed polypropylene to flow in creating a mechanical interlocking and improving the mechanical properties. The thermally stable biochar provided a compact char structure during combustion which prevented the heat and mass transfer between the polypropylene and the ambient O2 . Thermal stability of polypropylene was increased as a result of biochar inclusion, as observed in thermogravimetry.